GeSn alloys fabricated by modified sputtering deposition - Qian, Li (Nanyang Technological University, 2020)
Direct band-gap semiconductors have always been an interest to the research community in the area of photonics and optoelectronics. Most commonly used group IV semiconductors such as silicon and germanium have shown their capabilities in the application of microelectronics, however, lack in breakthroughs of the photon-electron related application because of the natural indirect energy band structure. Limitations in the photon-electron conversion lead to low effectiveness of their optoelectronic devices, which forces researchers to find substitutes of much higher cost and complexity. Most commercial and military optoelectronic devices are fabricated by direct band-gap group III-V compounds like GaAs, InSb, InAsSb, etc. Recently, group IV Ge1-xSnx alloy has been attracting great attention. By introducing a negative band-gap element Sn into Ge lattice, the band gaps decrease accordingly, especially the direct bandgap known as Г valley. Sufficient incorporation can transform the alloy from an indirect band-gap semiconductor to a direct band-gap semiconductor. 8% of Sn is a widely accepted value for this transformation. In this thesis, theoretical studies of bulk Ge1-xSnx and Ge1-xSnx/Ge quantum well were carried out by using the 8-band k.p method. The influences of growth condition and characterization environment were investigated, and the calculated parameters, such as spontaneous emission rate of the quantum well provide a good guide for the following experimental work on realizing direct band-gap GexSn1-x thin films. Instead of the widely reported epitaxial growth methods, a modified magnetron co-sputtering method was used to fabricate GexSn1-x thin films. To figure out the proper deposition parameters and environment, high-quality Ge and Sn thin films were separately fabricated at first. Various combinations of growth power, chamber pressure and growth time were performed to get high-quality films. The GexSn1-x thin films were fabricated on Si, Ge and GaAs substrates. Characterization techniques such as atomic force microscope, X-ray diffraction and Fourier transformation infrared microscopy were used to characterize the crystalline quality and optoelectronic properties. The peaks observed in the ω-2θ spectra confirm the successful synthesis of GexSn1-x thin films, and the shifted transmittance spectra demonstrate that the bandgap of the material can be tuned by varying the growth parameters. Optoelectronic applications based on the GexSn1-x thin films were explored. Metal-semiconductor-metal photoconductor, and GexSn1-x/n-GaAs hetero-structure photodetector were fabricated by standard optical photolithography technique associated with various deposition and etching methods. Current-voltage properties, photocurrent, photoluminescence, responsivity, and specified detectivity of the devices were characterized. The performance parameters of such devices show the high potential of the GexSn1-x alloys prepared by the modified co-sputtering for photodetection. Enhancement techniques have been applied to the GeSn/GaAs hetero-structure photodetectors. Instead of GeSn thin film, GeSn quantum dot sheet was fabricated on GaAs substrate by taking advantage of sputtering deposition and rapid thermal annealing. The enhancement factor of the specific detectivity for this configuration is around 3 to 6 times. Performances of such device were further optimized by fabricating a metallic 2-dimensional subwavelength hole array structure in the absorption window on the top of the GeSn quantum dot sheet. Surface plasmon resonance occurred when the light of specified wavelength interacted with the metallic structure, resulting in an enhancement of 2 to 4 times on the basis of GeSn quantum dot/GaAs hetero-structure photodetector. The final detectivity of the 2DSHA GeSn quantum dot/GaAs hetero-structure infrared photodetector reaches a considerable high value of 2.3×10^10 jones at 1450 nm.